Pharmacologically induced long-term enhancement in the hippocampus in vivo - Hayes, Jennifer (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2007)
The present study investigated the mechanisms underlying a pharmacologically induced long-term enhancement (LTE) of fast excitatory synaptic transmission in the CA1 region of the rat hippocampus in vivo. The role of cholinergic, glutamatergic and galaninergic receptors in the LTE induced by methoctramine, an M2 muscarinic acetylcholine (mACh) receptor antagonist, was investigated. Furthermore, the requirement for certain kinases in the induction and maintenance-expression of methoctramine LTE was assessed. Finally the ability of the Alzheimer’s disease (AD) associated protein; amyloid β (Aβ), to inhibit the LTE was evaluated. Experiments were carried out on adult male Wistar rats under urethane anesthesia. Electrodes were implanted in the CA1 region of the hippocampus and the excitatory postsynaptic potential (EPSP) amplitude was measured. Drugs were delivered either via a cannula into the lateral cerebral ventricle (i.c.v.) or systemically. Methoctramine, induced a rapid (generally <8 min onset) and persistent (>2hrs) enhancement of synaptic transmission. Consistent with this, another M2 preferring mACh receptor antagonist, gallamine, also enhanced synaptic transmission. In contrast BIBN-99, which is also an M2 mACh receptor antagonist failed to affect synaptic transmission, indicating that not all M2 mACh receptor antagonists share the ability to induce an (LTE).
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin